1985
DOI: 10.1093/ajcn/42.4.639
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin content of foods: effect on urinary excretion of 5-hydroxyindoleacetic acid

Abstract: Using a highly specific radioenzymatic assay we determined the serotonin concentration in 80 types of foods. The following fruits had a high serotonin concentration (mean +/- SEM) expressed in micrograms/g weight: plantain 30.3 +/- 7.5; pineapple 17.0 +/- 5.1; banana 15.0 +/- 2.4; Kiwi fruit 5.8 +/- 0.9; plums 4.7 +/- 0.8; and tomatoes 3.2 +/- 0.6. Only nuts in the walnut or hickory family had a high serotonin concentration expressed in micrograms/g weight; butternuts 398 +/- 90; black walnuts 304 +/- 46; Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(117 citation statements)
references
References 11 publications
5
110
0
2
Order By: Relevance
“…Moreover, many laxatives are made with seed and fruit extracts containing serotonins. Walnut and hickory have high levels of serotonins (25-400 mg/kg), while pineapples, bananas, kiwis, and tomatoes contain about 3-30 mg/kg (Feldman and Lee 1985). In the present study, C. tinctorius seeds were found to contain 4.3 mg/kg serotonin.…”
Section: Identification Of Four Major Chemical Compoundssupporting
confidence: 40%
“…Moreover, many laxatives are made with seed and fruit extracts containing serotonins. Walnut and hickory have high levels of serotonins (25-400 mg/kg), while pineapples, bananas, kiwis, and tomatoes contain about 3-30 mg/kg (Feldman and Lee 1985). In the present study, C. tinctorius seeds were found to contain 4.3 mg/kg serotonin.…”
Section: Identification Of Four Major Chemical Compoundssupporting
confidence: 40%
“…The high antioxidant capacity of kiwifruit may also reduce oxidative damage and consequently improve sleep quality. In addition, kiwifruit is one of the few fruits that has a high serotonin concentration (63), which may be another possible sleep-promoting mechanism of kiwifruit. However, the authors did not measure any of these biological compounds and therefore the mechanism of action remains unclear.…”
Section: Sleep-promoting Foods and Sleep Quality: Experimental Findingsmentioning
confidence: 99%
“…Strict attention to dietary intake of tryptophan may not be essential for diagnostic purposes, but is advisable if accurate monitoring of carcinoid patients is required for research studies. Many foodstuffs are rich in 5HTs,lo3, 104 and it has been demonstrated that excessive ingestion of bananas,6s.los.l06 pineapple 6S,IO? and watnutsl'" significantly increases urinary excretion of 5HIAA.…”
Section: Dietmentioning
confidence: 99%